Variability of formaldehyde in the Antarctic troposphere - Riedel, K.; Weller, Rolf; Schrems, Otto (1999)
The annual cycle of formaldehyde (HCHO) has been measured at a remote site in Antarctica in order to investigate seasonal and diurnal variations as well as chemical processes in the troposphere. The measurements have been performed in 1997 (March 1997 to January 1998) and in February 1999 at the German Antarctic research station Neumayer which is located at 70°39'S, 8°15'W. The obtained time series for formaldehyde in near-surface air clearly indicates the occurrence of diurnal and seasonal variations in Antarctica. It was found that HCHO concentrations vary from values below the detection limit (0.03 ppbv) to maximum values of 0.4 ppbv in winter and 0.7 ppbv in the austral summer. The observed concentrations show daily variations on certain days with maximums in early afternoon and minima during the night. It has been found that HCHO mixing ratios are significantly higher than so far predicted by photochemical models.